Draft Annual Plan 1978-79 Manipur - Government of Manipur (Government of Manipur, 1977)
The Draft Annual Plan for Manipur for 1978-79 outlines a comprehensive strategy aimed at socio-economic development, infrastructure enhancement, and poverty alleviation in the state. With a population of approximately 1.37 million, 70% of whom are engaged in agriculture, Manipur faces challenges including low road density, limited power availability, and widespread poverty, with a per capita income of Rs. 201 compared to the national average of Rs. 366. The plan emphasizes a two-pronged approach: rapid infrastructure development—including road networks, rural electrification, irrigation, and flood control—and employment generation through diversification in agriculture, horticulture, animal husbandry, forestry, and cottage industries. Sectoral proposals prioritize increasing agricultural productivity through double-cropping, oilseed introduction, maize and cotton cultivation, cold storage facilities, and enhanced training for farmers. Investments in education, health, and financial institutions aim to strengthen human capital and facilitate credit access for agriculture and small industries. The proposed development outlay totals ₹2,319.00 lakhs, with major allocations for Water and Power (₹1,144.87 lakhs), Agriculture and Allied Services (₹560.25 lakhs), Industries and Mining (₹450.00 lakhs), Transport and Communication (₹656.97 lakhs), and Social Welfare (₹384.70 lakhs). Emphasis is placed on disaster resilience, resource management, and improving connectivity to stimulate economic growth. The plan reflects a holistic approach, integrating immediate infrastructural needs with long-term productive capacity development to enhance living standards and promote sustainable development in Manipur.
Government of Manipur
Government of Manipur
Keywords: Manipur Annual Plan; Infrastructure Development; Agriculture and Allied Services; Water and Power; Transport and Communication; Social Welfare; Poverty Alleviation; Rural Electrification; Flood Control; Irrigation Projects; Industrial Development; Human Development